Ferulic acid from Lignocellulosic biomass: review - Noor Hasyierah, Mohd Salleh; Mohamed Zulkali, Mohamed Daud; Ku Syahidah Ku, Ismail (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 15th - 16th March 2008 at Putra Brasmana Hotel, Perlis.